Designing a Master of Accounting Study Program Profile Website Using the Wordpress Content Management System - Abdul Khaliq; Muhammad Iqbal; Dadang Iskandar Mulyana (Yayasan Sinergi Multidimensi Kreatif, 2024)
This article discusses designing a study program profile website using the WordPress Content Management System (CMS). Higher education has a need to present relevant and up-to-date information to prospective students, students, lecturers and the general public. A study program profile website can be an effective tool to meet these needs. The design method used in this research involves the needs analysis stage, interface design, selecting an appropriate WordPress theme, developing special features relevant to the study program, and testing functionality. Using the WordPress CMS as a content management platform makes it easy to manage and update content independently without requiring advanced programming skills. The result of this research is a study program profile website that is responsive, attractive, and easy to navigate. The features implemented include information about study programs, curriculum, lecturers, facilities and the latest news. Apart from that, it is equipped with a search feature to make it easier for users to find the specific information they want. Implementing the WordPress CMS as a content management platform provides time and cost efficiency benefits in managing a website. In addition, the flexibility and ease of adding or changing content ensures that the information presented is always up to date and relevant. In conclusion, designing a study program profile website using CMS WordPress is an effective solution for presenting up-to-date and relevant information to stakeholders in the academic environment. This research makes a contribution to the field of information technology, especially in the use of CMS platforms for efficient content management in the context of higher education.